PENGARUH PELATIHAN KERJA UNTUK MENINGKATKAN SUMBER DAYA MANUSIA YANG BAIKPENGARUH PELATIHAN KERJA UNTUK MENINGKATKAN SUMBER DAYA MANUSIA YANG BAIK (Jurnal Manajemen Kreatif dan Inovasi, 2023)
Human resources is the prime mover in a company, so it is important for companies to create something that could encourage each of its employees to produce achievements in their work. The purpose of this study was to determine training and motivation on employee performance. The method used in this study is using qualitative methods. Training functions is to provide opportunities for employees to increase their knowledge and insight so it can increase their work productivity and develop themselves, as well as contribute to the progress of the company in order to achieve the results set by the company. Training contributes positively to employee performance. Motivational factors play an important role in increasing employee productivity. More attention is needed on the selected training methods, facilities, equipment and the ability of the instructors to deliver training materials. An appeal to companies to be able to provide encouragement, encouragement, appreciation to employees who excel in order to increase employee motivation to complete the job as well.